Synthesis and enhanced visible-light photocatalytic activity of wollastonite/g-C3N4 composite. (February 2017) - Yao, Guangyuan; Sun, Zhiming; Zheng, Shuilin
Graphical abstract: Highlights: Wollastonite/g-C3 N4 was synthesized by a facile process. The Di/Wo(H + )-4:3 sample exhibited the optimal photoactivity. The role of wollastonite in the formation of Di/Wo(H + ) composites was discussed. The enhanced photocatalytic activities and enhancement mechanism were presented. Abstract: The novel wollastonite/g-C3 N4 composites were synthesized via a simple calcination and acid leaching process. The as-prepared photocatalysts were characterized by XRD, HRSEM, PL, UV–vis DRS, ESR and BET. The phtotocatalytic performance of the as-synthesizedcomposites was evaluated by the photodegradation of Rhodamine B under visible light irradiation. The visible-light photocatalytic activity of the as-prepared samples is much higher than that of pure g-C3 N4 . The Di/Wo(H + )-4:3 sample displays the optimal photocatalytic performance towards RhB under visible light and its reaction rate constant is 6.5 times that of pure g-C3 N4 . Meanwhile, the Di/Wo(H + )-4:3 presents a good durability and reusability. The improved photoactivity of the Di/Wo(H + ) composite could be attributed not only to its high surface area and porosity but also to the synergistic effect of the g-C3 N4 and wollastonite, which can effectively promote the separation of photogenerated electron-hole pairs and consequently enhanced its photoactivity.